Aplikasi Sulfur Terhadap Karakter Agronomi, Morfologi Dan Aktivitas Antioksidan Bawang Merah (Allium Ascalonicum L.) Dibudidaya Terapung - Novikar Saputra Idly; Susilawati Susilawati; Suwandi Suwandi; Oksilia Oksilia (Jurnal Penelitian Pertanian Terapan, 2024)
Floating agricultural cultivation is one of the right solutions for carrying out shallot cultivation in swamp areas. The aim of this research is to determine the effectiveness of sulfur application on the agronomic characters, morphology and phytochemical content of shallots (Allium ascalonicum L.). The research was carried out in May 2023 at the research pond of the Faculty of Agriculture, Sriwijaya University. The method used in this research was a completely randomized design with sulfur applications including : S1 (0 kg ha-1), S2 (30 kg ha-1), S3 (60 kg ha-1), S4 (120 kg ha-1), S5 (240 kg ha-1). The results of this research were that giving 60 kg ha-1 of sulfur to floating shallots had the best effect on the number of leaves, leaf length, crop growth rate, wet weight, and leaf chlorophyll content. Antioxidant activity can be predicted well from the additional sulfur dose in floating cultivation (R2: 89%) with an estimated optimum sulfur dose of 82.4 kg ha-1, 92.5 kg ha-1, and 134.5 kg ha-1. Air dry tuber weight can be predicted moderately (R2: 65%) with estimated optimum sulfur doses of 93 kg ha-1 and 79.3 kg ha-1.